Charge compensation in rare earth doped BaTiO3-based ceramics sintered in reducing atmosphere. Issue 16 (November 2020) - Zhang, Kai; Li, Lingxia; Wang, Menglong; Luo, Weijia
Abstract: Rare earth with radius ranges from 0.868 Å to 1.36 Å are introduced in BaTiO3 (BT) -based ceramics by solid-state reaction method, representing different charge compensation modes. Based on X-ray diffraction (XRD) and electron paramagnetic resonance (EPR) measurement, the behavior and solid solubility of La 3+, Ho 3+, Y 3+, and Yb 3+ in BT-based ceramics are systematically analyzed, then the charge compensation mechanism in this system is ascertained. Meanwhile, the function of dielectric properties with temperature at different concentrations is measured, which can be reasonably clarified by the Curie–Weiss and modified Curie–Weiss laws. Through the excellent dielectric performance, it is proved that rare earth ions play a role in improving the performance of BT-based ceramics, and the defect complexes formed therein are conductive to insulation resistivity in reducing atmosphere. Among all samples, the Yb 3+ doped BT-based ceramic possesses a relatively good comprehensive performance with high dielectric contant ( ε > 2600), low dielectric loss (tanδ = 1.83%) and high insulation resistivity (4.38 × 10 11 Ω·cm). Consequently, the defect compensation mechanism provides an effective regulatory method for BT-based ceramics, establishing a theoretical basis for multi-layer ceramic capacitor (MLCC).